An international questionnaire highlights and supports the case for including girls in Creatine Transporter Deficiency research - Chehowah, Carole; Mittelman, Audrey; des Portes, Vincent (Frontiers in Neuroscience, 2025)
Over the last 15 years, significant progress has been made for Creatine Transporter Deficiency (CTD) patients, with increased awareness and visibility, better diagnosis, and improved care. Research projects have paved the way for clinical trials on the horizon. However, girls with CTD have been overlooked. Because they are considered a negligible cohort with less serious symptoms compared to males, girls with rare X-linked disorders have never been a priority for diagnosis and research. This results in underdiagnosis, systematic exclusion from clinical studies, and a considerable impact on the development of female patients. As a patient association, Xtraordinaire aims to counter these beliefs and to show that females deserve as much attention as males. Our first initiative identified girls with CTD within our community and led to the development of an international questionnaire to collect more specific data in this population. Of the 22 families who completed the questionnaire, the delay between symptom onset (mean age 1.8 years) and diagnosis (mean age 11.8 years) highlighted the difficulty of diagnosis for girls, often given several wavering diagnoses before reaching a CTD diagnosis. Almost half of families (47%) had difficulties securing a specialist appointment. Our questionnaire emphasized that girls with CTD have identical symptoms to males and similar delays in development milestones. These data have generated interest, and researchers have started to include girls in their studies. We strongly believe that upcoming studies on females will enrich our knowledge, further our understanding of CTD, help better diagnose girls, and develop adapted treatments.